Immunoprecipitation and Western blot-based detection of protein O-GlcNAcylation in cells - Oumaima Ahmed; Malik Affar; Louis Masclef; Mohamed Echbicheb; Mila Gushul-Leclaire; Benjamin Estavoyer; David J. Vocadlo; El Bachir Affar (STAR Protocols, 2022)
Summary: Detection of protein O-GlcNAcylation could be challenging. By using the host-cell factor 1 (HCF-1), a known O-GlcNAcylated protein, we immunoprecipitated HCF-1 from transfected HEK293T cells or endogenous HCF-1 from HeLa cells to detect its O-GlcNAc levels by Western blotting. We also take advantage of RNAi or chemical inhibitors to modulate OGT and OGA activities before HCF-1 immunoprecipitation.For complete details on the use and execution of this protocol, please refer to Daou et al. (2011).